Role of Pilocarpine in Postmortem Interval Estimation - Shaima Sultana Memon, Shahid Nezam, Abdul Waheed, Hari Ram, Agha Shafique, Iqbal Ahmed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Estimation of time interval since death is an important aspect of forensic medicine, it is used as an evidence in both civil and criminal cases. There are multiple techniques used worldwide but reaction of pupil to chemical agents is currently the topic of interest. Studies on the role of pilocarpine in estimating the post-mortem interval (PMI) are very limited worldwide so the current study aimed to estimate the time interval since death using pilocarpine eye drops. Methods: An experimental Cross-sectional study was conducted at the department of forensic medicine and toxicology of a tertiary care hospital of Karachi (Autopsy Lab). The diameter of the pupil of each eye was measured using a Vernier caliper. After that 2% pilocarpine eye drops were administered to both eyes. About 10 to 15 minutes was allowed for pupillary reaction. The pupillary diameter was measured again after 25 minutes. The data was analyzed using Statistical Package for Social Science (SPSS) for Windows Version 22. p-value ≤ 0.05 was considered as significant. Results: The mean age of the study participants was 61 ± 13.4 years and reported significant association with the postmortem interval. The mean postmortem interval was 5 hours 42 minutes ± 3 hours 19 minutes. It has been noted that the longest duration of pupillary reaction was 16 hours 2 minutes. There was a strong correlation of postmortem interval with the change in pupillary diameter after pilocarpine drops. Soon after death, in initial 2 hours the change in pupillary diameter after pilocarpine was 98.8% while the percentage of pupillary reaction decreases as long as the time since death. After 16 hours of death there was no change in pupillary diameter after administering pilocarpine drops. Conclusion: It can be concluded that pupillary reaction after pilocarpine eye drops is significantly associated with time interval since death as 98.8% response was recorded in first two hours after death. The longest postmortem interval up to which the pupil can response to eye drop is 16 hours. Keywords: Pilocarpine, Postmortem interval, Pupillary reaction